META-PRASANGKA DALAM HUBUNGAN ANTARKELOMPOK POLA MAKAN: PERSEPSI PELAJAR VEGETARIAN - Junelyn; Martinus Danang Pamungkas (Departemen Psikologi, Universitas Negeri Padang, 2026)
Situated within the framework of social psychology and social identity theory, this research extends previous studies on meta-prejudice and intergroup relations (in-groups and out-groups). This study analyzes the forms of meta-prejudice and the factors influencing its formation among students at SMAS Maitreyawira Batam. The study employed a descriptive qualitative method, utilizing documentation, interviews, and observation as data collection techniques with eight informants. Data gathered from interviews were subsequently analyzed using the analytical methods of triangulation theory and contextualized against existing theories and prior research. The findings indicate the formation process of vegetarian student identity. Furthermore, they reveal the forms of meta-prejudice held by vegetarian students regarding non-vegetarians, specifically the perception that vegetarians are considered peculiar, fanatical, and failing to meet adequate nutritional criteria; vegetarian dietary patterns were also found to be associated with an individual's attitudes and behaviors. Finally, institutional norms were identified as a significant factor influencing the formation of the meta-prejudice phenomenon. The implications of this study are directed toward the development of more inclusive values and norms education and prejudice reduction strategies.